Phonetic Convergence, Language Talent, Personality and Attention - Lewandowski, Natalie; Jilka, Matthias (Frontiers in Communication, 2019)
Studies into phonetic adaptation rarely consider individual differences (IDs) on a cognitive and personality level between speakers as a direct source of adaptation variation. In order to investigate the degree to which the individual phonetic talent and further psycho-cognitive IDs of speakers affects phonetic convergence in a second language setting, 20 German native speakers were involved in two dialog tasks with two native speakers of English, a male speaker of American English and a female speaker of Standard Southern British English. The dialogs were quasi-spontaneous task-oriented interactions elicited with the Diapix picture-matching game. The English L2 learners were divided into a phonetically talented and less talented group based on their test results and evaluation in a preceding extensive language talent test battery. The acoustic analyses using amplitude envelopes revealed that talented speakers converged significantly more towards their English native speaking partners in the Diapix study. An additional analysis relates their degree of convergence to a range of personality and cognitive measures. The factors openness, neuroticism, Behavior Inhibition score and the switch costs in a Simon Test were significantly impacting the degree of phonetic convergence in the dialog study.